DIPLOMASI DIGITAL INDONESIA SEBAGAI ALAT PROMOSI PARIWISATA RAJA AMPAT - Suryanti, Made Selly Dwi; Sinaga, Melpayanty (Indonesian Association for International Relations, 2023)
This research describes Indonesia's position in promoting Raja Ampat tourism by using soft power in the form of digital diplomacy. For this reason, a qualitative method was used with an online interview approach and using the conceptual framework of digital diplomacy and tourism. The results of this study indicate that digital diplomacy regarding Raja Ampat's tourism potential is carried out using the branding